Die etos van die Hervormde Kerk in die derde millennium - Nel, Johan (HTS teologiese studies, 2015)
The ethos of the Reformed Church in the third millennium. This article aims at revisiting the ethos of the Netherdutch Reformed Church of Africa. There are concerns over the vast numbers of members, especially young members that leave the church. Special interest is taken in view of the ethos of the church in the third millennium. The author was curious about the understanding of members of the church as far as the ethos is concerned. A study which included two different groups within the church indicated that further investigation and research are inevitable in order to broaden the view on the future of the church even more. Factors such as the opinions of members of the church regarding the ethos and the question whether the understanding of the ethos has any impact on the declining of membership numbers could contribute to this debate.